Physical Properties of Aqueous Mixtures of Acetamide-LiCl Eutectic Ionic Liquids as a Function of Temperature and Composition - Liu*, Baoyou; Liu, Yaru (Asian Journal of Chemistry, 2014)
The density, conductivity and viscosity of aqueous solutions of acetamide-LiCl eutectic ionic liquid were investigated at atmospheric pressure and temperatures from (303.15 to 343.15) K and within the whole composition range. The density values decrease linearly with the increase of the mass content of water and the data decrease with increasing temperature. The mole volume (Vm) values were calculated from the experimental results. The perfect linear relationship between the Vm values and the mole fraction of water indicates that the studied mixtures are ideal solution. The viscosity values decrease sharply with the increase of the mass fraction of water in ionic liquid rich region and then tend to decrease gently in water rich region. The relationship between reciprocal of viscosity (1/h) and the mass fraction of water can be well fitted with a second-order polynomial equation. With the increase mole fraction of water, the conductivity values of the solution increase gradually first and then decrease dramatically and the highest conductivity values appear at about 0.940-0.958 mole fraction of water. The relationship between the conductivity and the mole fraction of water can be well described by a Castell-Amis equation.